2023
DOI: 10.1055/s-0043-1768719
|View full text |Cite
|
Sign up to set email alerts
|

Health Information Exchange: Understanding the Policy Landscape and Future of Data Interoperability

Abstract: Objectives: To review recent literature on health information exchange (HIE), focusing on the policy approach of five case study nations: the United States of America, the United Kingdom, Germany, Israel, and Portugal, as well as synthesize lessons learned across countries and provide recommendations for future research. Methods: A narrative review of each nation’s HIE policy frameworks, current state, and future HIE strategy. Results: Key themes that emerged include the importance of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The healthcare industry has witnessed the development of a multitude of personal health applications and remote monitoring devices to directly address the challenges related to healthcare facilities and the availability of service delivery, enabling on-demand and automated vital signs monitoring, medication tracking, and personalized health recommendations that are fundamental for effective and efficient self-management of potential diseases [ 72 , 73 ]. The interoperability of healthcare data and secure data transmission through Health Information Exchange (HIE) platforms has facilitated data sharing, thus enabling fast and reliable data analysis from a distance, reducing redundancies in data, and enhancing care coordination [ 74 ]. However, digital technologies have transformed healthcare delivery modes by expanding the landscape and improving outcomes.…”
Section: Digital Anti-aging Healthcare and Diet Managementmentioning
confidence: 99%
“…The healthcare industry has witnessed the development of a multitude of personal health applications and remote monitoring devices to directly address the challenges related to healthcare facilities and the availability of service delivery, enabling on-demand and automated vital signs monitoring, medication tracking, and personalized health recommendations that are fundamental for effective and efficient self-management of potential diseases [ 72 , 73 ]. The interoperability of healthcare data and secure data transmission through Health Information Exchange (HIE) platforms has facilitated data sharing, thus enabling fast and reliable data analysis from a distance, reducing redundancies in data, and enhancing care coordination [ 74 ]. However, digital technologies have transformed healthcare delivery modes by expanding the landscape and improving outcomes.…”
Section: Digital Anti-aging Healthcare and Diet Managementmentioning
confidence: 99%
“…In the survey paper of the Health Information Exchange (HIE) section, Holmgren et al presented the policy of five different countries (USA, UK, Germany, Israel and Portugal) in terms of HIE [24]. For each country, the authors reported the existing frameworks and the remaining considerations to be considered.…”
Section: One Health and Medical Informaticsmentioning
confidence: 99%
“…Interoperability Issues Achieving interoperability between different health IT systems is crucial for seamless data exchange and continuity of care , Aturamu, Thompson & Akintuyi, 2021. However, rural healthcare providers may use disparate systems that are not interoperable, leading to data silos and inefficiencies in information sharing between providers, hospitals, and other healthcare stakeholders (Holmgren et al, 2023). Data Security and Privacy Concerns, Rural healthcare organizations must comply with strict regulations regarding the security and privacy of patient health information, such as HIPAA (Health Insurance Portability and Accountability Act).…”
Section: Introductionmentioning
confidence: 99%